Design of Reduction Process of SnO2 by CH4 for Efficient Sn Recovery. Issue 1 (December 2017) - Ha, Hyunwoo; Yoo, Mi; An, Hyesung; Shin, Kihyun; Han, Taeyang; Sohn, Youhan; Kim, Sangyeol; Lee, Sang-Ro; Han, Jun; Kim, Hyun
Abstract We design a novel method for the CH4 reduction of SnO2 for the efficient recovery of Sn from SnO2 through a study combining theory and experiment. The atomic-level process of CH4 -SnO2 interaction and temperature-dependent reduction behavior of SnO2 were studied with a combination of a multi-scale computational method of thermodynamic simulations and density functional theory (DFT) calculations. We found that CH4 was a highly efficient and a versatile reducing agent, as the total reducing power of CH4 originates from the carbon and hydrogen of CH4, which sequentially reduce SnO2 . Moreover, as a result of the CH4 reduction of SnO2, a mixture of CO and H2 was produced as a gas-phase product (syngas). The relative molar ratio of the produced gas-phase product was controllable by the reduction temperature and the amount of supplied CH4 . The laboratory-scale experimental study confirmed that CH4 actively reduces SnO2, producing 99.34% high-purity Sn and H2 and CO. Our results present a novel method for an efficient, green, and economical recycling strategy for Sn with economic value added that is held by the co-produced clean energy source (syngas).